The value of Protein Induced by Vitamin K Absence or Antagonist-II (PIVKA) in predicting the efficacy of transhepatic arterial chemoembolization (TACE): A retrospective study: PIVKA in transhepatic arterial chemoembolization (TACE) - Shi, Qing; Ruan, Xinxin; Zhang, Zhuang; Xu, Jingui (Journal of Medical Biochemistry, 2025)
[Objective]: To investigate the value of AFP combined with degamma-carboxylprothrombin (DCP), vitamin K absence or antagonist-II (PIVKA) in predicting the efficacy of transhepatic arterial chemoembolization (TACE). [Methods]: The clinical data of 85 patients with hepatocellular carcinoma (HCC) who received TACE at our hospital between October 2021 and March 2023 were retrospectively analyzed. Changes in the serum AFP and DCP levels of patients before TACE and after two consecutive TACE operations were analyzed. The therapeutic effect of TACE was evaluated using the MRECIST criteria. The changes in AFP and DCP levels were compared with the imaging data from the same period (mRECIST criteria). The measurement data were tested for normality, and comparisons between two groups conforming to a normal distribution were performed by two-way independent sample t tests. The Mann‒Whitney U test was used to compare normally distributed data between the two groups. The χ2 test was used to compare the counting data between the two groups, and the Mann‒Whitney U test was used to compare the rank counting data between the two groups. Spearman correlation analysis was used to explore the correlation between mRECIST grade and AFP and DCP levels, and the value of each index in the diagnosis of patients in the remission group was analyzed by subject working characteristic curve analysis. [Results] According to the mRECIST criteria, 38 patients were in the remission group, and 31 were in the nonremission group. After treatment, the AFP and DCP levels in the remission group were significantly lower than those in the nonremission group (Z = -3.366 and -4.065, P < 0.05). There were statistically significant differences in △AFP, △DCP, △AFP%, and △DCP% between the remission group and the nonremission group (Z = -4.837, -5.597, -4.210, and -5.851, respectively; P < 0.001). The mRECIST stage was negatively correlated with △AFP and △DCP (RS= -0.552 and -0.593, P < 0.001). The area under the working characteristic curve of △AFP% was 0.796, that of △DCP% was 0.912, that of △AFP% + △DCP% combined was 0.921, and that of △AFP% + △DCP% had the greatest diagnostic value. [Conclusion]: Combined analysis of serum AFP and DCP levels before and after TACE can be used to evaluate the therapeutic effect of TACE in hepatocellular carcinoma patients.